Utilização de resíduos siderúrgicos como adsorventes de baixo custo no tratamento de efluentes contendo emulsões oleosas - Sara Vasconcelos dos Santos (2013)
The oily emulsions in general are formed by dissolution of mineral lubricants in water, widely used to protect metallic pieces and extend the life of machines and equipment, utilized in operations involving high wearing and frictional heating. The effluents contaminated by emulsions containing a large amount of recalcitrant organic compounds, insufficiently removed by conventional treatment processes. The treatment of organic contaminants and persistent chemicals by adsorption has proven effective and has been widely used. Flexibility and simplicity in operation and modeling of the system and insensitivity to toxic contaminants are characteristics of this process. However, a development of low cost adsorbents and of high adsorptive capacity for organic pollutants is desirable for greater diffusion of the technique. The use of steel waste for this purpose is promising due to rich composition in iron oxides and carbon, which impart favorable properties of organic fractions adsorption. The treatment of synthetic oily emulsions (1% v/v), based of emulsifiable lubricant, was realized by adsorption in steel wastes from wetcleaning of gases of blast furnace and steelworks. The Blast Furnace Sludge and Blast Oxygen Furnace Sludge, as are called, were physically, chemically and morphologically characterized, presenting predominance of different elements and phases in their compositions. The Blast Furnace Sludge presented a distributed composition of FeT (37,9%) in more oxidized forms, C (26,1%), SiO2 (11,2%) e CaCO3 (8,8%), and low concentrations of various metals, already in BOFS there was predominance of reduced phases of iron, FeT (55,4%), CaCO3 (18,5%), C (1,4%), SiO2 (1,2%) and elevated concentration in metals. In the treatment pH = 3, and concentrations of 60g/L of each waste, high removal efficiency was obtained for COT, DQO and turbidity, from the order of 98%, 98% and 99%, respectively, for both wastes. The adsorption mechanisms presented different behaviors, possibly related to different properties, like polarity and dominant interactions. After the adsorption, the Blast Furnace sludge was regenerated thermally, in oxidizing and inert atmosphere and in different temperatures. The wastes regenerated at 800ºC, in both atmospheres, maintained the removal percentage of DQO of approximately 98%, for the second and third cycle of adsorption. The union of wastewater treatment and use of waste steel, alia the reuse of these materials to the minimization of the use of landfills, to innovative treatment technologies and increased efficiency.